Changes in the Corticospinal Tract Beyond the Ischemic Lesion Following Acute Hemispheric Stroke: A Diffusion Kurtosis Imaging Study. Issue 2 (25th January 2020) - Yu, Xinfeng; Jiaerken, Yeerfan; Wang, Shuyue; Hong, Hui; Jackson, Alan; Yuan, Lixia; Lou, Min; Jiang, Quan; Zhang, Minming; Huang, Peiyu
Abstract : Background: The degeneration of the corticospinal tract (CST) in chronic stroke has been widely described using diffusion tensor imaging and correlates with the extent of motor deficits. However, only a few studies have reported the early degeneration in the distal CST during the acute stage of stroke and pathological changes in the distal CST have not been described. Purpose: To study the microstructural changes along the CST beyond the ischemic lesion in acute stroke using diffusion kurtosis imaging (DKI). Study Type: Prospective. Population: In all, 48 patients (26 males, 22 females; mean age 58.27 ± 12.89 years) with acute ischemic stroke. Sequence: A DKI sequence with three b‐values (0, 1000, and 2000 s/mm 2 ) at 3.0T MRI. Assessment: The kurtosis and tensor parameters were derived from DKI and were compared along the length of the CST beyond the ischemic lesion between the affected and unaffected hemispheres using both voxelwise and slicewise analysis. The degree of neurological deficits was evaluated using the National Institute of Health Stroke Score (NIHSS) and the Barthel index and the clinical outcome at 3 months was evaluated using a modified Rankin scale. Statistical Tests: Paired t ‐tests, a linear mixed model, and multivariate linear regression. Results: Voxelwise analysis demonstrated increased mean kurtosis, increased axial kurtosis, and decreased axial diffusivity in the affected CST, which were seen only at the level of the cerebral peduncle (all corrected P < 0.05). Slicewise analysis also demonstrated increased axial kurtosis in the cerebral peduncle of the affected CST (corrected P < 0.05). The axial kurtosis from slicewise analysis independently correlated with the motor component of NIHSS (β = 0.297, P = 0.040). Data Conclusion: Our findings suggest that early anterograde degeneration occurs along the axon direction in the distal CST in acute stroke, and can be detected using DKI. Moreover, acute axonal degeneration along the CST correlated with motor deficits. Level of Evidence: 2 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;52:512–519.